Analisis Kesalahan Berbahasa pada Spanduk dan Pamflet di Jalan Raya dalam Kajian Morfologi - Audina, Fitra; Dewi, Lusi Cantika; Septiandi, Muhammad Fichri; Angkat, Puri Andari; Arizki, Aqsol (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to identify language errors in the field of morphology on banners and pamphlets. The research uses a descriptive method with observation, photos, and notes to obtain data by observing language usage. Errors in language usage often occur in both spoken and written form, deviating from language rules and not in accordance with EYD (Improved Spelling). Language errors or language processes are closely related to the language learning process. Language errors occur in both spoken and written language, such as in the field of morphology. With these language errors, the analysis of language errors is very important. Language errors on banners on the highway in the field of morphology mostly relate to written language, including the use of standard and non-standard words. Based on the data found and analyzed, it can be concluded that errors in language usage in the field of morphology related to word writing are still often found in banner writings. This study examines eight data related to standard and non-standard word errors.